Pengaruh Game Online Terhadap Ahklak Siswa di SMPN 10 Kabupaten Bengkulu Tengah - M. Alif Erdiansyah; Edi Ansyah (Al-Bahtsu: Jurnal Penelitian Pendidikan Islam, 2025)
This study aims to determine the effect of online games on students' morals at SMP Negeri 10, Bengkulu Tengah Regency. The phenomenon of increasing intensity of online game use among teenagers raises concerns about the development of students' morals and social behavior. The method used in this study is a quantitative method with a descriptive correlational approach. The population in this study were all students in grades VII and VIII, with a sample of 80 students selected using purposive sampling techniques. Data were collected through closed questionnaires, interviews, and observations, then analyzed using a simple regression test. The results showed that there was a significant negative effect between the intensity of playing online games and students' morals. The higher the frequency of playing online games, the lower the level of students' fulfillment of social and religious norms that apply in the school and family environment. The conclusion of this study is that excessive use of online games can have a negative impact on students' morals, so supervision from parents and teachers is needed to limit and direct the use of games wisely.